We are responsible for what we have written and published - Лихова, Софія Яківна; Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Review of the Scientific-practical commentary of Criminal Code of Ukraine written by O. I. Motliakh, N. V. Maliarchuk, Iu. V. Kornieiev, L. A. Harbovskyi, H. V. Didkivska, T. O. Mudriak.